Dietary Habits and Caries Prevalence in Older Adults: A Scoping Review - Grigoria Gkavela; Eftychia Pappa; Christos Rahiotis; Panagiota Mitrou (Dietetics)
Caries is very common in the elderly as there are several aggravating factors, such as a decrease of the ability to self-care and, by extension, insufficient oral hygiene, a carious diet, limited exposure to fluoride, xerostomia, gingival recession, and limited access to dental care. This study aimed to review the dietary risk factors for root caries prevalence in older adults, from socially active people to frail patients. A comprehensive search strategy was used to select studies from PubMed and Scopus databases. Two evaluators performed data extraction, screening, and quality assessment independently. Only studies written in English were included. Root caries is prevalent in the elderly due to gingival recession and root exposure to the oral environment. Dietary risk factors significantly affect root caries prevalence in older adults, including a high intake of sugars and an alteration of their composition preference in this age group. Caries risk appears more significant in frail, institutionalized patients fed softer food or supplements.